Modelling electromagnetic responses of 2-D structures due to spatially non-uniform inducing fields. Analysis of magnetotelluric source effects at coastlines - Martinelli, Hilda Patricia (2003)
In previous works, we presented 2-D and 3-D magnetotelluric modelling methods based on Rayleigh-Fourier expansions. These methods are an alternative to finite-element and finite-difference techniques and are especially suitable for modelling multilayered structures, with smooth irregular boundaries. Here we generalize the 2-D method for the calculation of the electromagnetic response of 2-D structures to arbitrary, spatially non-uniform 2-D and 3-D inducing magnetic fields. These fields are characteristic of low- and high-latitude regions. We calculate the response to different 2-D and 3-D sources, of a 2-D structure representative of the conductivity distribution which could be found at a coastline, which includes deep conductive anomalies in the lower crust and upper mantle. Then, we investigate source effects, comparing these responses to that obtained for a uniform source. These effects become noticeable for periods greater than approximately 6 h and increase with the period of the source. They are highly dependent on the morphology of the source and also on the orientation of the external field relative to the strike direction of the structure. In various cases, they totally mask the uniform source response.